Effects of the Licorice Isoflavans Licoricidin and Glabridin on the Growth, Adherence Properties, and Acid Production of Streptococcus mutans, and Assessment of Their Biocompatibility - Katy Vaillancourt; Geneviève LeBel; Geneviève Pellerin; Amel Ben Lagha; Daniel Grenier (MDPI AG, 2021)
Pharmacological studies have linked a number of human health benefits with licorice due to its anticancer, anti-inflammatory, anti-oxidant, and antimicrobial properties. The aim of this study was to investigate the effects of licoricidin and glabridin, two major licorice isoflavans, on growth and virulence properties (biofilm formation, acid production, dextran production, adherence) of the cariogenic bacterium Streptococcus mutans. Moreover, the biocompatibility of these licorice compounds was assessed in an in vitro model of oral keratinocytes. We used a broth microdilution assay to show that licoricidin and glabridin exhibit a marked antibacterial activity against S. mutans. Glabridin and, to a lesser extent, licoricidin reduced the biofilm viability of S. mutans. In addition, glabridin decreased the production of dextran by S. mutans. The two licorice isoflavans attenuated the adherence of S. mutans to a saliva-coated hydroxylapatite surface, and reduced acid production from glucose. Lastly, depending on the concentrations tested, the two licorice isoflavans showed no or low toxicity toward oral keratinocytes. Within the limitations of this study, our data suggest that licoricidin and glabridin may be promising agents for controlling dental caries.